Dissolved oxygen determination in sewers using flow hydraulic parameters as part of a physical-biological simulation model. Issue 1 (18th November 2021) - Heydarzadeh, Reza; Tabesh, Massoud; Scholz, Miklas
Abstract: This paper aims to develop a model for calculating the hydraulic and water quality parameters of wastewater within sewers. Information from the wastewater collection network and the transmission line in Birjand were used to verify the model performance. The parameters used for modelling quality changes include the yield constant for biomass ( YH ), the maximum specific growth rate ( μH ), the saturation constant for dissolved oxygen ( KOG ) and the saturation constant for readily biodegradable substrate within a biofilm ( KSF ), as well as the Gauckler–Manning–Strickler coefficient ( n ). They were selected from references and were verified at the calibration stage comparing measurements with the modelling values. Inputs of the created model are the average concentrations of dissolved oxygen and chemical oxygen demand of the incoming wastewater, the flow rate of wastewater at the exit point of the network, physical characteristics of the pipes and the height of drops within the sewer network. The amount of dissolved oxygen at different positions of the sewer network was calculated. The acceptable calculated sum of squares of errors and the correlation coefficient ( R 2 ) of the calibrated model for dissolved oxygen were 1.6872 and 0.77, respectively. HIGHLIGHTS: A model was developed to calculate the hydraulic and qualitative parameters in sewers. The model was calibrated using the flow rate, organic strength and the dissolved oxygen. A sensitivity analysis of the dissolved oxygen change was performed. Dissolved oxygen was determined using the flow rate at the transmission line. The coefficient of flow change over time can be used to calculate dissolved oxygen.